Expectation and perception of nursing students in caring for patient with deteriorating: A descriptive qualitative study - Nur Umairah El Afifah Al Hisham; Rusila Ruslan (Palembang MediRose Publisher, 2024)
Introduction: Nursing students commonly exhibit low confidence levels when handling complex patient conditions, particularly those involving deteriorating health. Their lack of confidence and competence in managing deteriorating patients may potentially cause harm and even lead to fatal consequences if early recognition of such conditions is not made, given their role as primary responders in healthcare settings.Objective: This study aims to explore the expectation and percetiption of nursing students in caring for deteriorating patients.Methods: A descriptive, qualitative approach was employed, utilizing purposive sampling to select participants. Specifically, nursing students from a school in Pahang were chosen for this study. A topic guide was provided during interviews, employing a semi-structured approach with open-ended questions. Data obtained were analyzed using thematic analysis, resulting in the identification of themes and subthemes. Results: Findings revealed that 37.5% of the nursing students were not ready, while others felt prepared despite encountering various barriers and challenges. Three themes emerged: 1) unpredictable, 2) predictable, and 3) anticipated.Conclusions: In summary, the readiness of nursing students in providing care for deteriorating patients significantly influences the care received by the patient, both directly and indirectly. Despite struggling to adapt to challenges, the nursing students displayed willingness to provide nursing care.